2012
DOI: 10.1002/emmm.201100627
|View full text |Cite
|
Sign up to set email alerts
|

Emerging genetics of COPD

Abstract: Since the discovery of alpha-1 antitrypsin in the early 1960s, several new genes have been suggested to play a role in chronic obstructive pulmonary disease (COPD) pathogenesis. Yet, in spite of those advances, much about the genetic basis of COPD still remains to be discovered. Unbiased approaches, such as genome-wide association (GWA) studies, are critical to identify genes and pathways and to verify suggested genetic variants. Indeed, most of our current understanding about COPD candidate genes originates f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 101 publications
1
52
0
3
Order By: Relevance
“…Similarly, population studies indicate an association of SNPs near IL1RL1 on chromosome 2 and IL33 on chromosome 9 with the development of asthma (65)(66)(67), but to our knowledge, no similar associations have been reported for COPD thus far (68). Moreover, the present results suggest that environmental agents (i.e., viral infection) may alter IL-33 expression, making it likely that epigenetic approaches may be more informative than studies of gene sequence in identifying a basis for COPD-related differences in airway epithelial cells.…”
Section: Methodsmentioning
confidence: 69%
“…Similarly, population studies indicate an association of SNPs near IL1RL1 on chromosome 2 and IL33 on chromosome 9 with the development of asthma (65)(66)(67), but to our knowledge, no similar associations have been reported for COPD thus far (68). Moreover, the present results suggest that environmental agents (i.e., viral infection) may alter IL-33 expression, making it likely that epigenetic approaches may be more informative than studies of gene sequence in identifying a basis for COPD-related differences in airway epithelial cells.…”
Section: Methodsmentioning
confidence: 69%
“…Unfortunately, few studies have successfully unraveled the genetic predisposition and pathogenetic mechanisms for COPD 25. Dysregulation of miRNAs has been reported to be involved in the pathogenesis of pulmonary diseases, including COPD 26.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a fraction (∼20%) of smokers develop COPD, and some families have an increased risk to COPD, suggesting that host factors, likely inherited, modulate the risk for COPD from smoking [2]. Consistent with this concept, genome-wide association studies (GWAS), and candidate gene studies have identified COPD risk loci [3][5]. However, despite convincing evidence that inherited genetic variation conveys an increased risk of COPD in smokers, the relationship between these loci and the disordered biology of specific cell types within the lung is unclear.…”
Section: Introductionmentioning
confidence: 95%